2021
DOI: 10.3390/en14040988
|View full text |Cite
|
Sign up to set email alerts
|

Is the Alternative Energy Sector COVID-19 Resistant? Comparison with the Conventional Energy Sector: Markov-Switching Model Analysis of Stock Market Indices of Energy Companies

Abstract: The outbreak and rapid spread of the COVID-19 pandemic has hit the global financial markets, including the energy sector. Alternative energy belongs to the economy’s key sectors concerning environmental issues and seems to be a full-fledged alternative for fossil-based conventional energy. This paper aims to assess the impact of COVID-19 on the stock market indices related to the alternative and conventional energy sector. We use daily data on the Morgan Stanley Capital International (MSCI) Global Alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 61 publications
4
17
0
Order By: Relevance
“…It is also claimed by some sources that after the Covid-19 outbreak, there will be a positive acceleration in the solar industry [29]. Wang et al revealed the positive effects of Covid-19 pandemic based on the positive data showing the positive progress of some companies [28].…”
Section: Findings Confirming That the Solar Sector Is In A Positive Trendmentioning
confidence: 98%
“…It is also claimed by some sources that after the Covid-19 outbreak, there will be a positive acceleration in the solar industry [29]. Wang et al revealed the positive effects of Covid-19 pandemic based on the positive data showing the positive progress of some companies [28].…”
Section: Findings Confirming That the Solar Sector Is In A Positive Trendmentioning
confidence: 98%
“…Czech and Wielechowski [42] in their study evaluate the impact of COVID-19 on stock indices related to the alternative and conventional energy sector. The analysed indices decline as the government anti-COVID-19 policy becomes more stringent, but the relationship is statistically significant only in the high-volatility regime.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outbreak and quick spread of the COVID-19 pandemic hit global financial markets, including the energy sector. Czech and Wielechowski (2021) assessed the influence of the pandemic on stock indices connected with the conventional and alternative energy sectors. The analysed indices declined as the government anti-COVID-19 policy tightened, but the relationship was statistically significant only in the high variability regime.…”
Section: Literature Reviewmentioning
confidence: 99%